2022
DOI: 10.1108/lht-12-2021-0487
|View full text |Cite
|
Sign up to set email alerts
|

Librarian’s perception on data librarianship core concepts: a survey of motivational factors, challenges, skills and appropriate trainings platforms

Abstract: Purpose Data librarianship, or data-driven librarianship, is the combination of information science, data science and e-science fields and is gaining gradual importance in the library and information science (LIS) profession. Hence, this study investigates the data librarianship core concepts (motivational factors, challenges, skills and appropriate training platforms) to learn and successfully launch data librarianship services.Design/methodology/approach A survey method was used and the data were collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Since most participants mentioned they would start looking for online learning resources by themselves first, libraries should attempt to provide internal training to ensure librarians have more options for learning (Ashiq and Warraich, 2022). As for the suggestions to trigger librarians' learning interests, the learning backgrounds and purposes presented in Appendix 6 are useful before libraries introduce RPA technologies.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most participants mentioned they would start looking for online learning resources by themselves first, libraries should attempt to provide internal training to ensure librarians have more options for learning (Ashiq and Warraich, 2022). As for the suggestions to trigger librarians' learning interests, the learning backgrounds and purposes presented in Appendix 6 are useful before libraries introduce RPA technologies.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…From the perspective of job nature, acquisitions and collection management were the most frequently mentioned departments during the interviews. In addition to the specific departments, participants also suggested that librarians having responsibilities for data-related work would also be high potential users (Ashiq and Warraich, 2022). Besides, according to the literature, many other areas of library workflow have a high potential for RPA utilization, as summarized below. Electronic form processing – such as verifying submitted information, supplementing it with data from other sources, processing uploaded files, replying to submitters, and transferring data to relevant systems to follow up.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…Network of schools of public policy, affairs, and administration (NASPAA), an international accreditation association for graduate-level public administration programs, also called for a discussion of their roles in developing a new curriculum model for Master of Public Administration (MPA) and Master of Public Policy (MPP) for incorporating data science into the curriculum in 2019 (McFarland et al, 2019). Inspired by the call from NASPAA and similar recent trends in Library and Information Science (Ashiq and Warraich, 2022;Yew et al, 2022;Lo et al, 2017b;Chiu and Ho, 2022a, b), we present this work to address it by conducting research using a multifaceted approach to develop an MPA/MPP curriculum with a data science track by identifying the core areas and elective areas needed.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019). Inspired by the call from NASPAA and similar recent trends in Library and Information Science (Ashiq and Warraich, 2022; Yew et al. , 2022; Lo et al.…”
Section: Introductionmentioning
confidence: 99%